Digital media and mental health in adolescent athletes - Fiedler, R.; Heidari, J.; Birnkraut, T.; Kellmann, M. (Psychology of Sport and Exercise, 2023)
Although digital media are increasingly important for adolescent athletes, few studies explore their influence on mental health in this population. This study aimed to examine this relationship in 591 German adolescent athletes (aged 12-19 years) from 42 different sports. Longer daily social media usage was connected to increased negative affect and dysfunctional eating patterns. Similar results were found for cognitive-behavioral symptoms of excessive media usage and mental health. Structural equation modeling revealed these relationships were mediated by social comparison and quality of sleep. Higher athletic performance level was related to increased social comparison, but not to quality of sleep, negative affect, and dysfunctional eating. The negative relationship between excessive media usage and sleep was stronger in competitive and elite than in recreational athletes. Results imply digital media should receive attention when aiming to improve mental health in athletes. Relevant targets for future intervention could be social comparison and sleep.